Psychological well-being of sports managers: differences between experienced and future managers and the influence of gender, age, and family status - Radu Predoiu; Luca Mihai Grozav; Gabriela Szabo; Mihai Ciolacu; Andrzej Piotrowski; Davide de Gennaro; Răzvan Marian Bucătaru (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2026)
The purpose of the study. The study had two main aims: to compare the psychological well-being in experienced sports managers and future managers, and to examine how age, gender, marital status, and parental status are influencing the perceived well-being among experienced sports managers. Materials and methods. Sixty-one participants took part in the research, aged between 21 and 60 years, 40 male and 21 female managers (in the entire sample), of which 28 experienced sports managers (with a mean of 7.57 years in a managerial position) and 33 future sports managers. The Well-Being Assessment (Adult – 24 items) was used to measure eight facets of psychological well-being. Results. After independent t-test was performed, significant differences were found for Life Satisfaction and Life Evaluation (p = 0.024), respectively for Financial Evaluation and Stability (p < 0.001) between the two groups of managers, with experienced sports managers reporting higher scores. A series of Mann–Whitney (U) tests were conducted among experienced sports managers, to verify how gender, age, marital status and parental status are influencing managers’ psychological well-being. Conclusions. Female sports managers scored higher than experienced male managers for Character and Caring, and regarding the Financial Evaluation and Stability facet of well-being. Marital and parental status showed only subtle, non-significant trends in specific domains such as Life Satisfaction and Life Evaluation, Financial Evaluation and Stability, respectively Meaning and Purpose, while the younger group of sports managers reported higher scores on Character and Caring.